Real estate companies' size and the production of energy-efficient housing services: Evidence from Germany's apartment housing market - Claus Michelsen; Sebastian Rosenschon; Christian Schulz (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper investigates the effect of a housing company's size on the outcome of energetic refurbishment. We argue that economies of scale, economies of scope and effects of learning have an impact on the production of energy-efficient housing services. To test our hypothesis, we use unique data on 102,307 apartment houses in Germany. Besides owner characteristics and refurbishment effort, we introduce several control variables, to capture vintage, size and spatial effects. We find strong evidence for the presence of firm-specific, in particular size, effects on the energetic outcome of refurbishment. For example, large housing companies reduce real energy requirements of a building by 39.96% in the case of full refurbishment. In contrast, single-unit owners increase energy efficiency by only 15.93%. Moreover, the absolute differences between company types increase with refurbishment effort.
Keywords: R31; R32; Q48; 330